Well-being and death - Bradley, Ben, 1971- (Oxford : Oxford University Press, 2009)
Ben Bradley investigates what is good about life and what is bad about death. He argues that pleasure is what makes life go well and that death is bad for its victim because it deprives him of a continuing good life. Bradley considers intriguing related questions, including how death can be made less bad.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Life; Death